FROM COVID-19 TO PATIENT SAFETY: PRACTICE IN INDONESIA - Haerawati Idris (Indonesian Journal of Health Administration, 2022)
The December 2022 edition of the Indonesian health administration journal has been published. This time raised several topics about health system. Generally, the manuscripts submitted raise topics related to the issue of Covid-19. Other topics include access to health services, management programs, health insurance, and patient safety. Another topic of this edition also raises the issue of access to health services. Ainy (2022) The issue of Covid-19 is still a concern for researchers at this time. Covid-19 inspection services are still a necessity at this time. However, not all districts can prepare for this need. Imaniar (2022) reports that the availability of RT-PCR in Covid-19 tests is still limited at the district level. Since Covid-19, the use of online-based systems has increased. Murima reported (2022) that the use of telemedicine in health facilities during a pandemic greatly helped health service providers, but there were obstacles such as not being multidisciplinary and lack of knowledge in using technology.